THE ROLE OF ORGANIZATIONAL COMMUNICATION IN ENHANCING STRATEGIC PERFORMANCE - Assistant Lecture. Maha Farooq Ezzat (Scholars Digest Publishing, 2024)
This study aims to determine the level of organizational communication in healthcare organizations in Baghdad Governorate and the impact of organizational communication on organizational identity, the effect of organizational identity on strategic performance, and the impact of organizational communication on strategic performance. The descriptive survey method was used to issue questionnaires to the research sample. The survey sample was (280 employees of the Baghdad Provincial Health Organization. Two hundred seventy-three questionnaires were returned, six questionnaires containing missing values were deleted, and (17) were unsuitable due to outliers. The final total number of questionnaires analyzed was (250). The study concluded that the level of organizational communication in healthcare organizations is higher, the arithmetic mean is (3.803), and the arithmetic mean representing the degree of downward communication in higher-level organizations is (3.819). It is primarily affected by the arithmetic mean (3.803) of the organization's degree of upward communication. The study also found an essential positive relationship between organizational communication, organizational identification and strategic performance, and corporate identification, partially mediating this relationship. Furthermore, this study highlights the importance of considering organizational communication and identity in improving strategic performance in organizational settings. Overall, this study contributes to a deeper understanding of the complex interplay between organizational communication, identity, and strategic performance and provides valuable insights to organizational leaders and policymakers in healthcare organizations in the Baghdad Governorate.
Keywords: organizational communication, strategic performance, organizational identity, information flow.